Calculate: -16+6(x-5)=-6+2(5x-2)

Expression: $-16+6\left( x-5 \right)=-6+2\left( 5x-2 \right)$

Distribute $6$ through the parentheses

$-16+6x-30=-6+2\left( 5x-2 \right)$

Distribute $2$ through the parentheses

$-16+6x-30=-6+10x-4$

Calculate the difference

$-46+6x=-6+10x-4$

Calculate the difference

$-46+6x=-10+10x$

Move the variable to the left-hand side and change its sign

$-46+6x-10x=-10$

Move the constant to the right-hand side and change its sign

$6x-10x=-10+46$

Collect like terms

$-4x=-10+46$

Calculate the sum

$-4x=36$

Divide both sides of the equation by $-4$

$x=-9$